Does more favourable handling of the cerebrospinal fluid increase the diagnostic sensitivity of Borrelia burgdorferi sensu lato-specific PCR in Lyme neuroborreliosis?. Issue 4 (3rd April 2018) - Forselv, Kristine J. N.; Lorentzen, Åslaug R.; Ljøstad, Unn; Mygland, Åse; Eikeland, Randi; Kjelland, Vivian; Noraas, Sølvi; Quarsten, Hanne
Abstract: Background: Tests for direct detection of Borrelia burgdorferi sensu lato (Bb) in Lyme neuroborreliosis (LNB) are needed. Detection of Bb DNA using PCR is promising, but clinical utility is hampered by low diagnostic sensitivity. We aimed to examine whether diagnostic sensitivity can be improved by the use of larger cerebrospinal fluid (CSF) volumes and faster handling of samples. Methods: Patients who underwent CSF examination for LNB were included. We collected two millilitres of CSF for PCR analysis, extracted DNA from the pellets within 24 h and analysed the eluate by two real-time PCR protocols (16S rRNA and OspA). Patients who fulfilled diagnostic criteria for LNB were classified as LNB cases and the rest as controls. Results: Bb DNA in CSF was detected by PCR in seven of 28 adults with LNB. Two were Bb antibody negative. No Bb DNA was detected in CSF from 137 controls. Diagnostic sensitivity was 25% and specificity 100%. There was a non-significant trend towards larger CSF sample volume, faster handling of the sample, shorter duration of symptoms, and higher CSF cell count in the PCR-positive cases. Conclusion: We did not find that optimized handling of CSF increased diagnostic sensitivity of PCR in adults with LNB. However, our case series is small and we hypothesize that the importance of these factors will be clarified in further studies with larger case series and altered study design. PCR for diagnosis of LNB may be useful in cases without Bb antibodies due to short duration of symptoms.